Correction: Unsymmetrical 1, 1-diborated multisubstituted sp3-carbons formed via a metal-free concerted-asynchronous mechanism. Issue 48 (17th November 2015) - Cuenca, Ana B.; Cid, Jessica; García-López, Diego; Carbó, Jorge J.; Fernández, Elena
Abstract : Correction for 'Unsymmetrical 1, 1-diborated multisubstituted sp 3 -carbons formed via a metal-free concerted-asynchronous mechanism' by Ana B. Cuenca et al., Org. Biomol. Chem., 2015, 13, 9659–9664.